A Study on Oral Health of Children with Cardiac Diseases in Mashhad, Iran in 2004 - Mohammad Mahmoudi; Maryam Khordi Mood; Maryam Talebi; Shaili Alidad (Tabriz University of Medical Sciences, 2007)
Background and aims. Preventing oral disease is the most desirable way of ensuring good dental health for children with heart disease. Dental and gingival infections in patients with cardiac problems may lead to infective endocarditis. The aim of this study was to evaluate oral and dental health status in children with heart disease referred to a cardiac center compared with the control group. Materials and Methods. In this descriptive cross-sectional study, case group consisting of 100 patients 2-12 years old with heart disease were examined for oral and dental status in Pediatric Cardiac Center in Mashhad, Iran, in 2004. Fifty healthy children with the same age as the case group referring to the Department of Pedodontics, Mashhad Faculty of Dentistry served as the control group. For each patient, dental and medical history, dmft, DMFT, debris index, tooth brushing status as well as parental knowledge of infective endocarditis and their economic status was registered on a questionnaire. Statistical analysis was performed using Kruskal-Wallis, chi-square and t-tests. Results. There were no significant differences between case and control groups in dmft (3.92 ± 3.99 and 3.54 ± 3.33, respectively), DMFT (3.7 ± 4 and 1.47 ± 1.72, respectively) and their components. Tooth brushing status and debris index were significantly worse in the study group (P = 0.001 and P = 0.008, respectively). 35% of parents were aware of the importance of good oral health in cardiac children although none of them knew about infective endocarditis. Most of the parents in study group had low (30%) to medium (53%) economic status. Conclusion. In this study, the children with cardiac disease did not have a good oral and dental health status. Developing strategies toward preventive dental care of children with cardiac problems and informing their parents is suggested.